LEADERSHIP DEVELOPMENT IN THE COMMUNICATION BY BUDDHISM APPROADCH MINISTRY OF LABOUR’S ADMINISTRATORS - พระมหาบุญเลิศ อินฺทปญฺโญ วรรณกานต์ ขาวลาภ, เติมศักดิ์ ทองอินทร์, (Journal of MCU Social Science Review, 2017)
The objectives of this research were: 1. to study general situation of communication of Ministry of Labour, 2. to study leadership in communication of Ministry of Labour, and 3. to propose a model of leadership development in Buddhist approach communication of Ministry of Labour. The data were collected through in-depth interview with 39 experts consisting of monks, administrators from Ministry of Labour and experts and focus group discussion with 14 key-informants composed of Labour Ministry officials, employers, employees and labour volunteer. The results of the study found that: 1. The Ministry of Labour has a policy to move its organization communication to officials for accurate and relevant communication, and to people for understanding of the ministry responsibilities and affairs; labour law, acts, regulations and labour rights. The weaknesses were that the administrators lack of body of knowledge and skills in Buddhist approach communication and lack of policy in potential development for administrators in body of knowledge and skills in Buddhist approach communication. 2. Leadership is the process to be used by authority to encourage, lead and push the others to work or do things eagerly for achievement. Buddhist approach leadership means qualifications of the leaders that the Buddha stated in Dutiyapapanika Sutta; shrewd, capable of administering business and having good credit rating. 3. The proposed model of leadership development in Buddhist approach communication of Ministry of Labour was that; the Buddhist approach communication should be set as the individual development policy for administrative candidates, the training course in Dhamma should be set for administrators, communication course based on Buddhist approach should be set up, knowledge management should be arranged by internal and external experts, and the best-practice administrators in Buddhist approach communication should be praised and admired.